What Kind of “Green” do the Guests Want? An Exploration of Adoption of Luxury Hotel Green Room Attributes - Arisandi, Desi; Gao (Phoebe), Fei; Moi Loh, Chin (Organizations and Markets in Emerging Economies, 2023)
This study aims to provide insights for sustainability initiatives in Singapore luxury hotels. We explore the impact of green room attributes toward guests’ satisfaction and hotel selection. We surveyed 387 respondents to identify their preferences for green room attributes. Among different green room attributes, we find that younger travelers are satisfied with cloth laundry bags, while older travelers appreciate wooden keys. A female guest is more likely to enjoy eco-friendly food and beverages amenities, while a male guest is more likely to appreciate motion or occupancy sensors. With regard to choosing a hotel, those traveling for leisure and at an older age ranked service quality as more important. Female travelers appreciate cleanliness compared to room rates, and those with higher education ranked sustainability initiatives higher. The analysis of demographic factors can be referenced by the hospitality industry practitioners and the hoteliers of luxury hotels operators when they plan to implement green room features or marketing strategies targeted to a specific segment of customers. As for the greater aim, the research contributes to the literature that focuses on the rise of green consumption to support global sustainability initiatives.